P-O17 The Royal Stoke Green Pathway: a method to undertake safe UGI surgery during the COVID pandemic. (16th December 2021) - Ghassemi, Nader; Meilak, Joseph; McKay, Siobhan C; Bhatt, Anand; Durkin, Damien; Athwal, Tejinderjit
Abstract: Background: During the first wave of the COVID pandemic surgical services we paralysed globally, with cancellation of an estimated 28-million operations during the first 12 weeks. Worryingly, surgical patient with COVID were reported to have unacceptably high peri-operative mortality, approaching 25%. However, there was an urgent clinical need to progress with category 1 and 2 operations, to prevent disease progression and avoidable morbidity and mortality from non-COVID pathologies. During the second and subsequent waves of the pandemic it was vital to protect patients from peri-operative COVID whilst undertaking urgent surgery safely. Methods: Our centre developed a ring-fenced 'Green Pathway' for category 1 and 2 patients requiring surgery. Patients were treated in physically separate area of the hospital, with no interaction between COVID and non-COVID patients, healthcare staff or facilities. Patients self-isolated for 14-days prior to admission, and had pre- and peri-operative COVID RT-PCR tests. We assessed outcomes for patients immediately prior to the introduction of the Green Pathway (1/10/2020) and following implementation (31/12/2020) to assess safety. Textbook outcomes for pancreatoduodenectomy were compared to assess safety and quality. Other data suggests that UGI surgery couldn't continue in other hospitals from December 2020. Results: There were 47 admissions to surgical HDU following category 1 and 2 upper GI operations during the study; 31 pre-pathway (PP) implementation, and 16 green pathway (GP) patients. Median age 66-years (43-78 range) PP vs 65-years (range 42-74) GP, median ASA 3 vs 2. Median HDU length of stay (LOS) 5-days vs 7-days, and median hospital LOS 11.5-days vs 9-days for PP vs GP respectively. There were 6 cases of peri-operative COVID in PP cohort, and 1 in GP (contract following discharge). There was no mortality within either cohort. For the subgroup of patients undergoing PD: 10 patients PP, 6 patients GP, textbook outcomes were achieved in 90% vs 67% PP vs GP. Conclusions: The implementation of the Green Pathway at our institution enabled continuation of surgery for patients with category 1 and 2 operations during the COVID pandemic with a significant reduction in peri-operative COVID infection, no mortality and no increase in length of stay. The TO rate was lower with the GP (not statistically significant), but our 4-year institution TO rate is 70.3%, comparing favourably to other studies. This pathway has enabled safe continuation of urgent surgery during the pandemic and could be a model for adoption in other centres especially if there is resurgence of COVID cases during the coming winter.